1987
DOI: 10.1007/bf00450458
|View full text |Cite
|
Sign up to set email alerts
|

Comminuted Colles' fractures treated with external fixation

Abstract: In a prospective series of 75 patients the results of early external fixation of comminuted intraarticular Colles' fractures were studied. Comparison was made to a control group of 32 patients treated with plaster cast fixation. The groups were equal with regard to age, sex and fracture type. The treatment consisted of reduction in general anaesthesia or arm block followed by the application of a small external fixation device. The fixation lasted for five weeks after which the patients were allowed free exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Functional evaluation was performed applying the criteria of Gartland and Werley (1951) modified by Sarmiento et al (1975) as well as the criteria of Lidstr6m (1959) modified by Kongsholm and Olerud (1987). The functional outcome was excellent and good in 18/21 patients according to the criteria of Lidstr6m and 19/21 patients according to the criteria of Gartland and Werley.…”
Section: Resultsmentioning
confidence: 99%
“…Functional evaluation was performed applying the criteria of Gartland and Werley (1951) modified by Sarmiento et al (1975) as well as the criteria of Lidstr6m (1959) modified by Kongsholm and Olerud (1987). The functional outcome was excellent and good in 18/21 patients according to the criteria of Lidstr6m and 19/21 patients according to the criteria of Gartland and Werley.…”
Section: Resultsmentioning
confidence: 99%
“…One group received an exercise instruction for the shoulder, elbow, wrist and fingers and the other group received both the exercise instruction and occupational therapy (Table 1) [5,18] at cast removal by 5 weeks, and after 3 and 9 months ( Table 2). The grip strength was measured using a "My gripper", which is shown to be very reliable [18] and the scoring was corrected for dominant compared with nondominant hand [2,9]. X-rays were taken at the accident and emergency ward on arrival, after reduction and at day 11, because earlier reports have shown that most fractures dislocate within the first 2 weeks [1,16].…”
Section: Methodsmentioning
confidence: 99%
“…No patient had substantially decreased function, and all the patients who had been working Discussion Smith's fracture in which all or part of the articular surface is displaced proximally and volarly, and in which the proximal carpal row is subluxated, is extremely unstable. The literature on external fixation of this type of injury is scarce, whereas several authors have reported favorable results of treating unstable Colles' fractures by external fixation (Cooney 1983, Vaughan et al 1985, Kongsholm and Olerud 1987. We found that the external fixator effectively maintains the reduction of unstable Smith's fractures.…”
Section: Resultsmentioning
confidence: 63%